L’Amazonie entre les myriades d’expériences et les politiques publiques dominantes - Neli Aparecida de Mello-Théry (Confins)
This article examines the challenge of thinking a new development model for the Brazilian Amazon, especially addressing public action nowadays. Region that lies at the crossroads of several attempts that sometimes coexist, but are often opposed. On the one hand, the Brazilian Amazon remains subject to decisions of dominant public and private actions that repeat traditional models of economic development at any cost. On the other, since the 1990s, it has been the site of hundreds of so-called sustainable experiments. Between these two contradictory worlds, the local population, merged with migrants, calls for recognition of their desires and their vision of development.